Pubic sector unionism in Leyte effects of public sector unionism in employee and organizational performance - Bandal, Bezie Mae; Berico, Jocel Marianne; Hilvano, Maita Isabel; Mercado, Cybil I; Udtohan, Angeli; Exconde, Amy Joan E. (2016)
This study examines how public sector unions influence the overall performance of government employees. Results of the research show that unions influence organizational performance by providing CNA incentives and organizing programs which can improve the working relations of the employees and promote employee welfare that will in turn impact the employee and its organizational performance. Moreover, unions should focus on the intrinsic factors such as programs that offer opportunities for personal development because this can significantly enhance productivity. One significant implication of this finding is for the management and the union to maintain a harmonious relationship.
Undergraduate research (Bachelor of Science in Management) -- University of the Philippines, Tacloban.